Pengaruh Warna Dan Waktu Pemasangan Perangkap Terhadap Populasi Hama Lalat Buah Di Tanaman Cabai - Jacob Julius Lawalata; Yuliana Magayung (Median : Jurnal Ilmu Ilmu Eksakta, 2026)
Fruit flies locate their host plants by responding to visual cues, particularly color, and chemical cues, such as fruit volatiles. These environmental factors influence host selection, feeding activity, mating behavior, and oviposition. This study aimed to evaluate the effects of trap color and trap installation time on the population of fruit flies captured in chili pepper fields. The experiment was conducted in August 2021 at a farmer-owned chili plantation in Doyo Baru Village, Waibu District, Jayapura Regency, Indonesia. A factorial experiment was arranged in a Randomized Complete Block Design (RCBD) with two treatment factors. The first factor was trap installation time, consisting of daytime (07:30–17:30 Eastern Indonesia Time, WIT) and nighttime (18:00–07:00 WIT). The second factor was trap color, consisting of yellow, green, and red traps. Data were analyzed using analysis of variance (ANOVA), and treatment means were compared to determine significant differences among treatments. The results demonstrated that daytime trap installation significantly increased the number of fruit flies captured compared with nighttime installation. Yellow traps consistently capture more fruit flies than green and red traps, indicating a stronger visual attraction to this color. A significant interaction between trap installation time and trap color was observed for male fruit fly captures and the total fruit fly population. The combination of daytime trap installation and yellow traps (J1W1) produced the highest capture rate, indicating that this treatment is the most effective for fruit fly monitoring and can support integrated pest management strategies in chili pepper cultivation.